Pelatihan Metode Pembelajaran Index Card Match dan Card Sort untuk Meningkatkan Kreativitas Guru Di Desa Boleng - Hijrat, Kasim; Guhir , Asliat H; Wahab, Farida; Akhmad , Tasyrifany; Siti Asiyah (INTEGRATIF: Jurnal Pengabdian Kepada Masyarakat, 2024)
This service activity aims to provide training in the Index Card Match and Card Sort learning methods to increase the creativity of teachers in Boleng Village. This activity is carried out in three stages, including planning, implementation (presentation of material and simulation) and discussion and evaluation. The results of interviews with teachers who took part in the training, on average, said that taking part in this training could motivate them to increase creativity so that teachers could apply it in learning to create a pleasant learning atmosphere and increase student activity in the learning process.. The results of observations also show that the teachers were very enthusiastic and active in participating in this training from start to finish. The teachers are even very fluent in simulating the application of this type of learning method to encourage enthusiasm for learning. The Index Card Match and Card Sort methods have been proven to increase teacher creativity and create a learning atmosphere that is fun and easy for students to accept and makes them more enthusiastic, active and motivated to participate in teaching and learning activities. It is hoped that all training participants can increase their creativity and carry out various innovations to create a fun and active learning atmosphere for students.